DIMENSI METRIK GRAPH LOBSTER Ln (q;r) - DONY GUMILAR, PANDE GDE; IDA HARINI, LUH PUTU; SARI, KARTIKA (E-Jurnal Matematika; Vol 2 No 2 (2013), 2013)
The metric dimension of connected graph G is the cardinality of minimum resolving set in graph G. In this research, we study how to find the metric dimension of lobster graph Ln (q;r) . Lobster graph Ln (q;r) is a regular lobster graph with vert i ces backbone on the main path, every backbone vertex is connected to q hand vert i ces and every hand vertex is connected to r finger vert i ces, with n, q, r element of N. We obtain the metric dimension of lobster graph L2 (1;1) is 1, the metric dimension of lobster graph L2 (1;1) for n > 2 is 2.
Keywords: lobster graph; metric dimension; resolving set